PERANCANGAN PERMAINAN GAME BALAPAN MOTOR MENGGUNAKAN MACROMEDIA FLASH 8.0 (Information Technology and Telematics, 2013)
Technological developments in the field of computers led many people to develop a work useful to yourself and others. Similarly, in the field of games or game applications. Game is very loved by the public and not look at age. Be it old, young, men, women love it. In addition to the fun and exciting, the game also can relieve fatigue after running the day-to-day activities. More recently, the game can also be an indirect means of education for children - children younger than 3 to 6 years. It could be a counting game, guess the picture, puzzle, and others - others. Game or the game is something that can be played by certain rules so that no one wins and no one loses, usually not serious in the context of the purpose of refreshing. Playing the game has to be said as a life style for today society. Starting from the age of children to adults was like a video game. It is all due to playing video games is fun. To design application programs Games Games Racing Motor, the writer uses Macromedia Flash 8.0 due to make a simple animation or game using Macromedia Flash 8, the required script is not as complicated as other programming languages. In making animations or games with Macromedia Flash 8, the drawing process, processing audio files, animations and scripts can all be done with this software so that the software is very efficient in many ways.  Keywords: Game, Program application, Macromedia Flash 8.0